State-Managed International Voluntary Service The Case of Japan Overseas Cooperation Volunteers - Okabe, Yasunobu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book addresses two issues of state-managed international voluntary service (SMIVS)$1 (Bits contributions and advantages/disadvantages$1 (Bby the case study of Japan Overseas Cooperation Volunteers (JOCV). Until now, the literature has given little attention to SMIVS and Asian international voluntary service (IVS). Proposing the concept of SMIVS, this is the first book in English to focus on JOCV and IVS managed by the Japanese government. The book is organized into two parts. In Part I, the authors, including scholars, former volunteers, and practitioners, explore the contributions of JOCV to the development in host communities, personal and professional development of volunteers, and Japanese civil society. In Part II, the authors analyze how JOCV creates advantages such as multilevel support by the Japan International Cooperation Agency (JICA), a Japanese government aid agency, and disadvantages such as the weak expertise of volunteers. The authors$1 (Btheoretical approaches cover capacity development, social capital, gift theory, and institutional theory, and their methodologies include statistical analysis of survey data, interview-based anthropological interpretation, and single/comparative case study. This combination of multiple approaches and methodologies is a strong feature of the study reported here. Thanks to state management, as the book demonstrates, JOCV can facilitate mutual benefits between volunteers and host communities, enhancing the human capital of the former and contributing to the socioeconomic development of the latter. It also shows that Japanese volunteers blend into host communities well, respecting and learning their social values and perspectives. This achievement is accomplished to the extent that collaborative and equal interpersonal relationships are nurtured between the volunteers and local people, including counterparts. Thus, this book helps to reduce inequality and stereotypes in IVS, with implications for other state-managed IVS.s
Foreword -- Introduction: JOCV as a State-managed international voluntary service -- Transitions in the 56 years of JOCV: Needs, service and cooperation -- Part I: Contributions of State-Managed International Voluntary Service -- JOCV$1 (Bs contribution to capacity development: Insights from case studies -- The Water Security Action Team (W-SAT) in Africa -- Revisiting the JOCV post in Cameroon -- Hearts, Minds, and Sentiments: The Volunteers Program in the Immunization Program in Bangladesh and the Chagas Diseases Control Project of Honduras -- Shocked and angry volunteers -- Giving Back to Society by Former JOCV -- Sports and Development$1!#((Btentative$1!#) (B-- What Do Volunteers Receive? Interpreting the Reciprocal Feelings of JOCV through Gift Theory -- Part II: Advantages and Disadvantages of State-Managed International Voluntary Service -- Strengths and Weaknesses of the State-Managed International Voluntary Services: The Case of JOCV -- The Long Journey of Development Cooperation across Four Continents -- Country Office as Part of the JICA Volunteer Program: Background and Its Implementation in Bhutan -- Winter Camp for Highland Schoolchildren in Bhutan -- International Volunteering under the Spread of the Covid-19: Insights from Evacuated JOCV -- Roles of JOCVs in School Health Education Program in Ghana: From the Perspective of Host Organizations -- Japanese volunteers in the Philippines: A story of friendship and human connection -- From my experience of working with JOCV in Cameroon -- Delegation of Agriculture and Rural Development of Bangangte, Cameroon -- Part III: Conclusions -- Breaking the iron cage: Understanding legitimacy claims for international development volunteering -- Conclusions.s
Keywords: Economic development; Personnel management; International relations; Development Studies; Human Resource Development; International Relations